Determination of quality compounds in Some of Iraqi honey types - Salman, Mohammed A.; AL-Mossawi, Aum-El-Bashar H.; Al-fekaiki, Dhia F. (Journal of Kerbala for Agricultural Sciences, 2019)
This study was conducted on different types of honey brought Collected From Basrah, Maysan, Najaf, Karbala, Babylon, Wasit, Baghdad, Diyala, Kirkuk and Sulaymaniyah Included : The quality-related compounds of honeys samples were Determinate within the permissible limits Including consisit of proline, diastase, hydroxylmethyl furfural (HMF); and vitamin C. honey content of proline the highest value was 687.34 mg kg-1 in Karbala region and the lowest value in Najaf region 295.34 mg kg-1, And diastase number the highest was 14.36 unit In Basrah region and the lowest diastase number in Babylon region 8.67 unit ,The hydroxymethyl furfal was the highest value in Babylon region 41.54 mg kg-1 while the lowest value in Basrah and Baghdad honey 12.35 Mg kg-1 each, the highest value of vitamin C 350.23 mg kg-1 in Najaf region and the lowest value in Maysan region 190.54 mg kg-1